Travelling‐wave ion mobility mass spectrometry and negative ion fragmentation of hybrid and complex N‐glycans. (23rd September 2016) - Harvey, David J.; Scarff, Charlotte A.; Edgeworth, Matthew; Pagel, Kevin; Thalassinos, Konstantinos; Struwe, Weston B.; Crispin, Max; Scrivens, James H.
Abstract : Nitrogen collisional cross sections (CCSs) of hybrid and complex glycans released from the glycoproteins IgG, gp120 (from human immunodeficiency virus), ovalbumin, α1‐acid glycoprotein and thyroglobulin were measured with a travelling‐wave ion mobility mass spectrometer using dextran as the calibrant. The utility of this instrument for isomer separation was also investigated. Some isomers, such as Man3 GlcNAc3 from chicken ovalbumin and Man3 GlcNAc3 Fuc1 from thyroglobulin could be partially resolved and identified by their negative ion fragmentation spectra obtained by collision‐induced decomposition (CID). Several other larger glycans, however, although existing as isomers, produced only asymmetric rather than separated arrival time distributions (ATDs). Nevertheless, in these cases, isomers could often be detected by plotting extracted fragment ATDs of diagnostic fragment ions from the negative ion CID spectra obtained in the transfer cell of the Waters Synapt mass spectrometer. Coincidence in the drift times of all fragment ions with an asymmetric ATD profile in this work, and in the related earlier paper on high‐mannose glycans, usually suggested that separations were because of conformers or anomers, whereas symmetrical ATDs of fragments showing differences in drift times indicated isomer separation. Although some significant differences in CCSs were found for the smaller isomeric glycans, the differences found for the larger compounds were usually too small to be analytically useful. Possible correlations between CCSs and structural types were also investigated, and it was found that complex glycans tended to have slightly smaller CCSs than high‐mannose glycans of comparable molecular weight. In addition, biantennary glycans containing a core fucose and/or a bisecting GlcNAc residue fell on different mobility‐ m/z trend lines to those glycans not so substituted with both of these substituents contributing to larger CCSs. Copyright © 2016 John Wiley & Sons, Ltd.